2022
DOI: 10.1002/vrc2.268
|View full text |Cite
|
Sign up to set email alerts
|

First case of pithomycotoxicosis in sheep in the Netherlands

Abstract: Pithomycotoxicosis, commonly known as facial eczema, is a hepatogenous photosensitisation in grazing ruminants caused by intake of sporidesmin‐containing spores of the saprophytic fungus Pithomyces chartarum. Although this is a significant sheep disease in various countries in the world, it is rarely seen in Europe, and has been reported only once in the Netherlands, but in cattle. In October 2019, both sheep and lambs in a flock of 50 breeding sheep showed clinical signs of photosensitisation, including oedem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Pithomycotoxicosis is a hepatogenous photosensitisation in grazing ruminants caused by the intake of sporidesmin-containing spores of the saprophytic fungus Pithomyces chartarum that was confirmed for the first time in sheep in The Netherlands in 2019 [8,48]. Further cases were confirmed in 2020 and 2021.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…Pithomycotoxicosis is a hepatogenous photosensitisation in grazing ruminants caused by the intake of sporidesmin-containing spores of the saprophytic fungus Pithomyces chartarum that was confirmed for the first time in sheep in The Netherlands in 2019 [8,48]. Further cases were confirmed in 2020 and 2021.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…Early reports of animal deaths due to facial eczema date back to the late 1800s (Gilruth 1908), but the link between the disease and P. chartarum was only established in 1958 (Percival and Thornton 1958). Although the fungus occurs in other countries (Collin et al 1998;Dijkstra et al 2022;Pinto et al 2005), it is most problematic in the North Island of New Zealand (Di Menna et al 2009; Cuttance, Mason, and Laven 2021; Lawrence et al 2022) where, in contrast to other locations including the South Island, high proportions of P. chartarum isolates have the ability to produce sporidesmin (Collin, Odriozola, and Towers 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It requires moisture for sporulation (Mitchell et al 1959;Brook 1963), with heavy or continuing rainfall reducing its occurrence (Mitchell et al 1959). It has been suggested that climate change may increase the distribution and abundance of P. chartarum both in New Zealand (Di Menna et al 2009;Dennis et al 2014;McRae et al 2018) and western Europe (Dijkstra, et al 2022). Our study aimed to improve upon previous evaluations of the potential effects of climate change on facial eczema in New Zealand by developing a simple model of P. chartarum's temperature and rainfall requirements for sporulation, comparing its results to historical spore count data, then using it to predict how the prevalence of high spore counts-and by implication facial eczema-may change in the future.…”
Section: Introductionmentioning
confidence: 99%